Analyzing the Paraphrasing Techniques in Academic Writing Skills and the Paraphrasing Challenges Across Gender - Aprianto, Dedi; Sutarman, Sutarman; Ofara, Wafika (Universitas Pendidikan Mandalika, 2024)
Gender differences is assummed as the general individual’s differences that exists and catches an attention of many aspects in ELT. Writing techniques could have examined and yielded the potential facts in gender differences on the development of writing proficiency in English language learning. The study aims at identifying paraphrase techniques in gender differences and to explore the challenges the students encountered. A Mixed method research design was carried out. The participants of this study were 33 male students and 34 female students for writing test and 5 male students and 5 female students for interview. Data collection invloved the distribution of writing tests to the participants and doing interview. The findings showed that the frequency pertentages for male students NC 14%, Mi.R 27%, Mo.R 28%, SR 31% & for female students NC 31%, Mi.R 21%, Mo.R 29%, SR 37%. The most frequent paraphrase technique employed by male and female students is moderate revision (SR). Then, male students (57,73%) are more dominant than female students (41.32%) in using syntactical paraphrase, male students (37,65%) more frequent than female students (32,62%) in using semantic paraphrase, female students (26.06%) are more frequent than male students (4.62%) in using organizational paraphrase. The paraphrase challenges found on how to organize the ideas, problems of source text comprehension, problems of stylistic styles of writing, grammar or rules of sentences and vocabulary knowledge (Language Proficiency-Based Problems).